2015
DOI: 10.1177/0363546515574061
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Secondary Intra-articular Injuries With Time to Anterior Cruciate Ligament Reconstruction

Abstract: Increasing time from injury to ACLR was associated with increased incidence of secondary injury seen in the trochlea, lateral femoral condyle, medial tibial plateau, and medial meniscus. Separate analyses of patient age and preinjury activity level showed similar findings, thus supporting the primary analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 34 publications
4
46
0
2
Order By: Relevance
“…However, motion in the knee joint occurs across multiple planes of motion [2], and the stability of the knee is maintained by additional primary and secondary stabilizing structures that function to constrain the knee in the threedimensional context of motion [3]. ACL injuries are frequently accompanied by concomitant injuries to these stabilizing structures, and the resultant multifactorial instability has been shown to increase the risk of developing osteoarthritis (OA) [4][5][6]. Arthroscopic ACL reconstruction is widely accepted as the treatment of choice to address this problem, particularly for young patients with a high activity level and those who fail to cope with instability [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, motion in the knee joint occurs across multiple planes of motion [2], and the stability of the knee is maintained by additional primary and secondary stabilizing structures that function to constrain the knee in the threedimensional context of motion [3]. ACL injuries are frequently accompanied by concomitant injuries to these stabilizing structures, and the resultant multifactorial instability has been shown to increase the risk of developing osteoarthritis (OA) [4][5][6]. Arthroscopic ACL reconstruction is widely accepted as the treatment of choice to address this problem, particularly for young patients with a high activity level and those who fail to cope with instability [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with findings from a study of 616 participants that reported more meniscal injury in patients who underwent ACLR more than 3 months after injury and more cartilage injury in those who received ACLR more than 6 months from injury (Razi et al, 2013). Similarly, a large study of 1434 individuals found a relationship between an increased period of time from injury to surgery and higher rates of concomitant joint injury when presenting for ACLR, including injury to meniscus and joint surfaces (Ralles, Agel, Obermeier, & Tompkins, 2015). People with concomitant injury to other knee structures at the time of ACLR report higher rates of osteoarthritis 10 to 20 years later (Claes et al, 2013;Keays, 2010;Magnussen et al, 2009;Murray et al, 2012;Øiestad et al, 2009;van Meer et al, 2015) and poorer patient-reported outcomes after ACLR including more knee pain, symptoms, poorer function and reduced QOL (Barenius et al, 2010;Cox et al, 2014;Dunn et al, 2015;Gerhard et al, 2012;Neuman et al, 2008;Røtterud et al, 2012;Røtterud et al, 2013).…”
Section: Time From Injury To Surgerymentioning
confidence: 98%
“…Similarly, a large study of 1434 patients found a relationship between an increased period of time from injury to surgery and higher rates of concomitant joint injury when presenting for ACLR, including injury to meniscus and joint surfaces (Ralles et al, 2015). Concomitant meniscus and cartilage injury have been associated with an increased likelihood for self-reported knee symptoms, pain, function and poorer QOL 2 to 16 years after ACLR (Barenius et al, 2010;Cox et al, 2014;Dunn et al, 2015;Gerhard et al, 2012;Neuman et al, 2008;Røtterud et al, 2012;Røtterud et al, 2013).…”
Section: Time From Injury To Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…186 Injuries in the medial meniscus are also more common after initial ACL injury. 160,186 ACL injury with concomitant meniscal damage has been associated with worse subjective outcomes as well as increased prevalence of osteoarthritis. 17,40,102 ACL injuries with concurrent meniscal damage requiring surgical intervention significantly shortens professional sports careers comparing to an ACL injury alone.…”
Section: Incidence Of Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%